Cross-Sectional and Longitudinal Associations Among Children’s Interpersonal Trust, Reputation for Trustworthiness, and Relationship Closeness - Li, Qinggong; Li, Zhuocheng; Zhang, Wenyu; Wang, Yang; Heyman, Gail D. (Frontiers in Psychology, 2021)
Interpersonal trust plays a crucial role in the formation and maintenance of social relationships. The present cross-sectional and longitudinal research examines the development of interpersonal trust judgments with reference to (1) the trustee’s reputation of being trustworthy, and (2) the nature of the trustor’s personal relationships with the trustee. There were 194 7- to 13-year-olds who participated in the first wave of the study, and 107 of those individuals also participated in two subsequent waves across a two-year period. Both cross-sectional and longitudinal results showed that with age, reputation for being trustworthy becomes less important and personal relationships become more important. We also found that personal relationships played a greater role in interpersonal trust evaluations for girls than for boys. These findings indicate that the way children make trust evaluations becomes increasingly relationship-specific over time and is more relationship-specific for girls than for boys.